The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1529-8817.2004.03126.x
|View full text |Cite
|
Sign up to set email alerts
|

PHYLOGENY OF AULACOSEIRA (BACILLARIOPHYTA) BASED ON MOLECULES AND MORPHOLOGY1

Abstract: The phylogeny of 67 populations representing 45 species of Aulacoseira Thwaites was estimated by maximum parsimony methods using a combination of nucleotide sequence data and qualitative and quantitative morphological characteristics of the silica cell wall gathered primarily from original observation by LM and SEM. A new type of character using continuous quantitative variables that describe the ontogenetic-allometric trajectories of cell wall characteristics over the life cycle (size range) of diatoms is int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…Vegetative cells that then begin a new cycle again are in the upper size range of the species-specific interval [16]. Size reduction is typically accompanied by a change in the shape of the frustules [17][18][19][20], which leads to pronounced morphological allometry, a process typical of nearly every diatom population in natural habitats or cultured strains. Pappas et al [19] recently reported that variation in the empirical morphospace of most pennate diatom species relates to allometry as a result of the size reduction that occurs over successive vegetative cell divisions.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetative cells that then begin a new cycle again are in the upper size range of the species-specific interval [16]. Size reduction is typically accompanied by a change in the shape of the frustules [17][18][19][20], which leads to pronounced morphological allometry, a process typical of nearly every diatom population in natural habitats or cultured strains. Pappas et al [19] recently reported that variation in the empirical morphospace of most pennate diatom species relates to allometry as a result of the size reduction that occurs over successive vegetative cell divisions.…”
Section: Introductionmentioning
confidence: 99%
“…comm., 23 January 2008). It is important to note that phylogenetic analysis applies equally well to both molecular and morphological characters, including the traditional qualitative and quantitative features of the diatom cell wall (e.g., Cox and Williams 2006;Edgar and Theriot 2004;Theriot 1992). Hopefully the recent infusion of phylogenetic analysis into molecular diatom studies will spill over into morphological studies as well.…”
Section: Species Concepts In Diatom Systematicsmentioning
confidence: 99%
“…Simonsen and should be considered a separate species, which they named Aulacoseira skvortzowii Edlund, Stoermer & Taylor. Recent molecular studies have suggested that A. skvortzowii and another Aulacoseira species occurring in Lake Baikal, Aulacoseira baicalensis (Meyer) Wislouch (Babanazarova et al 1996;Popovskaya et al 2002), are the closest among living forms to extinct taxa of the genus and may have separated from each other within the lifetime of the lake (i.e., less than 25 million yr) (Sherbakova et al 1998;Edgar and Theriot 2004). However, this does not necessarily mean they are endemic, because spore-forming species similar to A. skvortzowii have been discovered in other Asian sites, including high mountain lakes Bondarenko 2001, 2004), Lake Khanka/Xingkai (Genkal and Schure 2000), and River Amur (Likhoshway et al 2004).…”
mentioning
confidence: 99%